Postprandial Effect of a High-Fat Meal on Endotoxemia in Arab Women with and without Insulin-Resistance-Related Diseases - Al-Disi, Dara; Al-Daghri, Nasser; Khan, Nasiruddin; Alfadda, Assim; Sallam, Reem; Alsaif, Mohammed; Sabico, Shaun; Tripathi, Gyanendra; McTernan, Philip (Nutrients, 2015)
This study determined the effects of a high-fat meal on circulating endotoxin and cardiometabolic indices in adult Arab women. The cohort consisted of 92 consenting Saudi women (18 non-diabetic (ND)) control subjects; Age 24.4 ± 7.9 year; body mass index (BMI) 22.2 ± 2.2 Kg/m2), 24 overweight/obese (referred to as overweight-plus (overweight+)) subjects (Age 32.0 ± 7.8 year; BMI 28.5 ± 1.5 Kg/m2) and 50 type 2 diabetes mellitus (T2DM) patients (Age 41.5 ± 6.2 year; BMI 35.2 ± 7.7 Kg/m2). All were given a high-fat meal (standardized meal: 75 g fat, 5 g carbohydrate, 6 g protein) after an overnight fast of 12–14 h. Anthropometrics were obtained and fasting blood glucose, lipids, and endotoxin were serially measured for four consecutive postprandial hours. Endotoxin levels were significantly elevated prior to a high-fat meal in the overweight+ and T2DM than the controls (p < 0.05). Furthermore, the postprandial cardiometabolic changes led to a more detrimental risk profile in T2DM subjects than other groups, with serial changes most notable in glucose, triglycerides, high density lipoprotein-cholesterol (HDL-cholesterol), and insulin levels (p-values < 0.05). The same single meal given to subjects with different metabolic states had varying impacts on cardiometabolic health. Endotoxemia is exacerbated by a high-fat meal in Arab subjects with T2DM, accompanied by a parallel increase in cardiometabolic risk profile, suggesting disparity in disease pathogenesis of those with or without T2DM through the altered cardiometabolic risk profile rather than variance in metabolic endotoxinaemia with a high-fat meal.